2022
DOI: 10.1111/cts.13398
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory variants in a novel distal enhancer regulate the expression of CYP3A4 and CYP3A5

Abstract: The cytochrome P450 3As (CYP3As) are abundantly expressed in the liver and metabolize many commonly prescribed medications. Their expression is highly variable between individuals with little known genetic cause. Despite extensive investigation, cis-acting genetic elements that control the expression of the CYP3As remain uncharacterized. Using chromatin conformation capture (4C assays), we detected reciprocal interaction between a distal regulatory region (DRR) and the CYP3A4 promoter. The DRR colocalizes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…The rs115025140 variant also showed a trend towards reduced statin e cacy. While rs111266634 variant showed a reduced reporter expression in luciferase reporter assay without affecting CYP3A4 and CYP3A5 gene expression [20]. This study also reported that the rs776744 and rs776742 variants, which are not exclusive in AAs, were associated with TAC trough concentrations in Chinese KTRs.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The rs115025140 variant also showed a trend towards reduced statin e cacy. While rs111266634 variant showed a reduced reporter expression in luciferase reporter assay without affecting CYP3A4 and CYP3A5 gene expression [20]. This study also reported that the rs776744 and rs776742 variants, which are not exclusive in AAs, were associated with TAC trough concentrations in Chinese KTRs.…”
Section: Discussionsupporting
confidence: 60%
“…Collins and colleagues [20] reported variants in the CYP3A DRR that increased expression of CYP3A4 and CYP3A5 mRNA and/or protein. The rs115025140 variant also showed a trend towards reduced statin e cacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, mutations in the neighboring CYP2C18 gene are associated with ultrarapid metabolism of escitalopram, which is associated with decreased escitalopram levels at a similar or greater extent to those caused by the wellestablished ultrarapid CYP2C19 * 17 allele. Analogous cases have been described for a haplotype within the UGT2B locus, which associates with decreased glucuronidation of clozapine (67), and for a novel distal enhancer in the CYP3A locus that impacts statin efficacy and tacrolimus clearance (68). It is of utmost importance to identify the functionally important genetic variants within the novel CYP2C:TG and UGT2B haplotypes, as the linkage of marker SNPs could drastically differ between ethnic groups.…”
Section: Effects Of Novel Haplotypes In Cismentioning
confidence: 81%